2011
DOI: 10.1016/j.jocs.2010.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Twitter mood predicts the stock market

Abstract: Abstract-Behavioral economics tells us that emotions can profoundly affect individual behavior and decision-making. Does this also apply to societies at large, i.e. can societies experience mood states that affect their collective decision making? By extension is the public mood correlated or even predictive of economic indicators? Here we investigate whether measurements of collective mood states derived from large-scale Twitter feeds are correlated to the value of the Dow Jones Industrial Average (DJIA) over… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
2,435
9
59

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 3,974 publications
(2,533 citation statements)
references
References 41 publications
30
2,435
9
59
Order By: Relevance
“…They also found that disagreement between the posted messages was associated with increased trading volume. More recently, Bollen et al (2011) found that Twitter mood predicted more than 80% of daily volatility of closing values of the Dow Jones Industrial Average. This would confirm Nofsinger's argument that social mood may cause an increase of decisions biased by optimism or pessimism that can considerably influence aggregate investment and business activity, even reflecting future economic activities (Nofsinger (2005)).…”
Section: Background and Hypothesesmentioning
confidence: 99%
See 2 more Smart Citations
“…They also found that disagreement between the posted messages was associated with increased trading volume. More recently, Bollen et al (2011) found that Twitter mood predicted more than 80% of daily volatility of closing values of the Dow Jones Industrial Average. This would confirm Nofsinger's argument that social mood may cause an increase of decisions biased by optimism or pessimism that can considerably influence aggregate investment and business activity, even reflecting future economic activities (Nofsinger (2005)).…”
Section: Background and Hypothesesmentioning
confidence: 99%
“…Therefore, while our results cannot contribute to formulate a general theory of the link of press and markets, they can provide important clues to understand the 'social construction' of pessimism between press and markets. Among the limitations, it is important to note that press pessimism and market behaviour could be also conditioned by other media, such as the new social media and the Internet (see the recent study on Twitter by Bollen et al (2011)). Further investigation is needed to compare behaviour and impact of various media and provide a more precise analysis of the 2008/2009 crisis (e.g., see Preis et al (2010)).…”
Section: Closing Remarksmentioning
confidence: 99%
See 1 more Smart Citation
“…relationships and decision making and are therefore analysed in many research projects. The automatic detection of emotions in text allows for a broad range of applications, such as forecasting movie box office revenues during the opening weekend [14], 3D facial expression rendering based on recognized emotions in text [5], stock prediction [4], and helping to understand consumer views towards a product [3].…”
Section: Introductionmentioning
confidence: 99%
“…Such a rapid development of microblog industry has led to a great interest in sentiment analysis of the information published by the microblog users [1]. In fact, tentative studies have already been conducted to analyze the sentiment of messages in Twitter, blogs and Google search queries to predict stock market, product sales, consumer spending, and movie sales [2]- [7].…”
Section: Introductionmentioning
confidence: 99%